The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1999
DOI: 10.1007/s002960050100
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal manifestations with panniculitis - a hospital based study on 62 patients in Kuwait

Abstract: The study describes 62 patients seen over a period of 4 years mainly presenting with an acute inflammatory ankle arthritis/periarthritis associated with panniculitis. Based upon the clinical characteristics of panniculitis two distinct categories could be defined. These included patients with characteristic lesions of erythema nodosum, seen in 51 (82%), the idiopathic form in 29 (57%), and secondary EN in 22 (43%). Associated conditions included Behçet's disease, oral contraceptive pills, pregnancy and penicil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…It is suggested that T-cell immune response is involved in the pathogenesis of WCD. [2][3][4] In our patient, histochemistry staining showed lymphocytic cells in endobronchitis. Comparing tocyclosporine A, cyclophosphamide can decrease both T cell and B cell functions and replication.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…It is suggested that T-cell immune response is involved in the pathogenesis of WCD. [2][3][4] In our patient, histochemistry staining showed lymphocytic cells in endobronchitis. Comparing tocyclosporine A, cyclophosphamide can decrease both T cell and B cell functions and replication.…”
Section: Discussionsupporting
confidence: 51%
“…Previous case reports showed cyclosporine A can be effective to resolve fever and painful subcutaneous nodules, and it can decrease high serum concentrations of interferon‐gamma and soluble interleukin‐2 in WCD patients. It is suggested that T‐cell immune response is involved in the pathogenesis of WCD . In our patient, histochemistry staining showed lymphocytic cells in endobronchitis.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Weber–Christian disease is the most serious form of panniculitis, with systemic manifestations, and has been only exceptionally described in the pediatric age group 1,24–28 . Seventy‐five percent of the cases occur in women after the second decade of life 26,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Lipophagia and granulomas led to confusion in the context of erythema nodosum, but focal necrosis of fat cells is not typical for it [3]. Erythema nodosum has been classi ed as predominantly septal panniculitis, unlike ndings in PWCD being classi ed as lobular panniculitis [10,11].…”
Section: Case Presentationmentioning
confidence: 99%